New Insight Into the Evaluation of Abnormal Left Ventricular Wall Motion - Nakamura, Yoichi (Cardiology and Cardiovascular Medicine, 2021)
Background: Previous predictors of mechanical dyssynchrony using echocardiography has not improved refractory heart failure in patients treated with cardiac resynchronization therapy. It was hypothesized that the spatially and temporary continuous information of the whole endocardium is required when the mechanical dyssynchrony is assessed using echocardiography. This study aimed to examine differences in the locus of the centroid of the left ventricle between wall motion abnormality. Methods: Twenty-seven patients with dilated cardiomyopathy and 45 old myocardial infarction patients with aneurysm were compared with 188 individuals with normal wall motions. In an off-line system, the centroid of the three-dimensional left ventricle was defined as the central point between both centroids calculated from four- and two-chamber images using an original application. Results: The locus of the centroid of the left ventricle (LCGLV) in the normal group showed a horizontally inverted β shape, whereas this shape was absent in the other groups. When corrected by left ventricular end-systolic volume, the total and each directional length of LCGLV in the abnormal wall motion groups were clearly reduced compared with those recorded in the normal group. The acceleration of the centroid was also reduced in the abnormal wall motion groups. Multiple linear regression analysis with a stepwise method revealed a corrected antero-posterior shift of the centroid of left ventricle by left ventricular end-systolic volume and N-terminal pro-brain natriuretic peptide, which strongly correlated with the LVEF (adjusted R2: 0.6818, p≤2.2 X 10-16). Conclusion: Use of the LCGLV provides novel insight into the evaluation of abnormal left ventricular contractions.